Aspidistra extrorsa (Asparagaceae), a new species from limestone areas in Guangxi, China - Nong, Dong-Xin; Huang, Yu-Song; Lin, Chun-Rui (Phytotaxa, 2018)
Aspidistra Ker Gawler (1822: t. 628) is a genus native to eastern and southeastern Asia. It includes over 170 species, and the number rapidly increased since 1980 (Tillich 2005, 2006, 2008, Liu et al. 2011, Lin et al. 2012, 2013, 2015, Meng et al. 2014, Hu et al. 2014, Huang et al. 2015, Liang et al. 2016).